Exploring Listening Strategy Usage In Senior High School Online Learning - Mandaku, Silvia Chaterin Theresya; Nikijuluw, Renata C. G. V. (MATAI: International Journal of Language Education, 2023)
The article examines the application of listening tactics in online learning. Listening is one of the core abilities in English that students must learn. This ability cannot be isolated from language learning. In order to master a listening ability, both the teacher and the students must devise an appropriate technique, especially in an online learning environment. According to the expert, there are numerous tactics that instructors might use, such as metacognitive strategies and cognitive strategies that incorporate bottom-up and top-down thinking. As a result, the writer thinks that this work will be valuable in assisting instructors in selecting and implementing suitable listening practices in online learning scenarios.